Why pandemic response is unique: powerful experts and hands‐off political leaders. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to show that 2009 H1N1 "swine" influenza pandemic vaccination policies deviated from predictions established in the theory of political survival, and to propose that pandemic response deviated because it was ruled by bureaucratized experts rather than by elected politicians.Design/methodology/approach – Focussing on the 2009 H1N1 pandemic, the paper employs descriptive statistical analysis of vaccination policies in nine western democracies. To probe the plausibility of the novel explanation, it uses quantitative and qualitative content analyses of media attention and coverage in two deviant cases, the USA and Denmark.Findings – Theories linking political survival to disaster responses find little empirical support in the substantial cross‐country variations of vaccination responses during the 2009 H1N1 pandemic. Rather than following a political logic, the case studies of media coverage in the USA and Denmark demonstrate that the response was bureaucratized in the public health agencies (CDC and DMHA, respectively). Hence, while natural disaster responses appear to follow a political logic, the response to pandemics appears to be more strongly instituted in the hands of bureaucratic experts.Research limitations/implications – There is an added value of encompassing bureaucratic dynamics in political theories of disaster response; bureaucratized expertise proved to constitute a strong plausible explanation of the 2009 pandemic vaccination response.Practical implications – Pandemic preparedness and response depends critically on understanding the lessons of the 2009 H1N1 pandemic; a key lesson supported by this paper is that expert‐based agencies rather than political leaders are the pivotal actors.Originality/value – This paper is the first to pinpoint the limitations of political survival theories of disaster responses with respect to the 2009 pandemic. Further, it is among the few to analyze the causes of variations in cross‐country pandemic vaccination policies during the 2009 H1N1 pandemic. Acknowledgements : This paper was made possible by funding from the Danish Research Council (2009‐2014) for the study of the politics of natural disasters and from the US National Science Foundation for study of global infectious disease response (Grant No. SES‐0826995; 2008‐2011). The authors wish to thank Ann Keller and Chris Ansell of the University of California, Berkeley, for their support and encouragement and the journal's anonymous reviewers for their insights and comments.